Monoclonal antibodies for organ transplantation: prospects for the future. - Waldmann, H (1988)
Monoclonal antibodies (MoAbs) have the potential to facilitate the induction of transplantation tolerance. Realization of this potential requires both a better understanding of the cellular events concerned with rejection and tolerance, and a more detailed approach to improving antibodies for therapy. This report reviews work in our laboratory directed toward these goals.